Toward Long-Term Sailing Robots: State of the Art From Energy Perspectives - Sun, Qinbo; Qi, Weimin; Liu, Hengli; Ji, Xiaoqiang; Qian, Huihuan (Frontiers in Robotics and AI, 2022)
Sailing robots can contribute significantly to maritime surface exploration, due to its potential for long range and long duration motions in the environment with abundant wind. However, energy, as the critical factor for their long-term missions, shall be carefully investigated, so as to achieve sustainability in distance and time. In this survey, we have conducted a comprehensive investigation on numerous sailing robots, developed in academia and industry. Some of them have achieved long-term operation and some are motivated by, but still on the way to this ambitious goal. Prototypes are grouped in each team, so as to view the development path. We further investigate the existing design and control strategies for energy sufficiency from three perspectives: actuation, harvesting and energy management. In propulsion and steering, i.e. two major actuations, researchers have accumulated effective sail and rudder designs. Motorized propeller and wave-glider-inspired mechanism also contribute as compliments for propulsion. Electricity harvesting based on solar or wind energies is also discussed to gather more power from nature. Pros and cons in strategies of energy management, which are valuable tools to enhance power utilization efficiency, are elaborated. This paper is hoped to provide researchers in long-term robotic sailing with a comprehensive reference from the perspectives of energy.